EFEKTIVITAS PENAMBAHAN PROLACZYME PADA PAKAN KOMERSIAL TERHADAP PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Tania Serezova Augusta; Deby Setyani; Kristina Kristina (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2020)
The utilization of effective and efficient feed given for growth is an indicator of successful fish cultivation. Enzyme activity is one of affects the growth rate of fish factors. Therefore, it is expected the addition of the enzyme of feed increases the growth and utilization of Nile Tilapia's (Oreochromis Niloticus) significantly. The study was to determine the effectiveness of prolaczyme dosage addition to the commercial feed fish on Nile tilapia's (Oreochromis niloticus) growth performance. This research was conducted from June to July 2020 on Palangka Raya, Central Kalimantan. This study used completely randomized method 3 treatments and 3 repetitions, tilapia's fish seeds size 2.07-2.23 cm with a container (15 fish/basin) water volume of 50 liters, and 1 month maintenance time. The results of the calculation of absolute length growth at the end of the study showed that treatment C was higher 5.30 cm compared to treatment A was 3.71 cm and treatment B was 4.59 cm. The results of the calculation of the absolute weight growth at the end of the study also showed that treatment C was higher at 2.41 gr compared to treatment A was 0.99 grand treatment B was 1.52 gr. The FCR value shows that treatment C worth 1.77 is better than treatment A worth 3.33 and treatment B worth 2.44. The results of water quality temperature, pH, and dissolved oxygen (DO) both at the beginning and at the end of the study showed a range that tilapia could still tolerate for growth.